Antimicrobial Activity Test of Methanol Extract of Haliclona sp. from Sibolga Waters - Ulfa Mashitah; Dwi Suryanto; Kiki Nurtjahja (Jurnal Penelitian Pendidikan IPA, 2024)
Haliclona sp. is a genus of demosponges in the family Chalinidae. Demospongiae are a type of sponge that lives in marine environments and is known for its unique, often branching skeletal structure. The use of antibiotics has led to the selection of pathogenic microorganisms in humans that are more resistant to many types of drugs, resulting in poorer treatment outcomes in cases of infection. Bacteria can become resistant to antibiotics due to improper dosing, inaccurate diagnosis, and inappropriate use of antibiotics against the causative bacteria. This study aims to determine the antimicrobial activity of the methanol extract of Haliclona sp. as an inhibitor of pathogenic microbes. This research employs a descriptive method with antagonistic testing. The results of the methanol extraction process of the symbiotic bacteria in Haliclona sp. produced a thick, dark brown extract. The results of the antagonistic test showed that the clear zones formed on the three test microbes were categorized as strong.